Cover Image. Issue 15 (26th December 2019) - Makhubela, T.V.; Kramers, J.D.; Scherler, D.; Wittmann, H.; Dirks, P.H.G.M.; Winkler, S.R.
Abstract : The cover image is based on the Original Article* Effects of long soil surface residence times on apparent cosmogenic nuclide denudation rates and burial ages in the Cradle of Humankind, South Africa by Tebogo Vincent Makhubela** et al., https://doi.org/10.1002/esp.4723 .***